Respuesta :
[tex]\huge \ \rm ༆ Answer ༄[/tex]
let's solve ~
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:5(4 + x) = 3(3x - 1) - 9[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:20 + 5x = 9x - 3 - 9[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:9x - 5x = 20 + 3 + 9[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:4x = 32[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:x = 32 \div 4[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:x = 8[/tex]
Answer:
The value of x is 8.
Step-by-step explanation:
[tex]{\star{\tt{\underline{\underline{\purple{CONCEPT : -}}}}}}[/tex]
Here, we will use the below following steps to find a solution using the transposition method:
- Step 1 :- we will Identify the variables and constants in the given simple equation.
- Step 2 :- then we Simplify the equation in LHS and RHS.
- Step 3 :- Transpose or shift the term on the other side to solve the equation further simplest.
- Step 4 :- Simplify the equation using arithmetic operation as required that is mentioned in rule 1 or rule 2 of linear equations.
- Step 5 :- Then the result will be the solution for the given linear equation.
[tex]{\star{\tt{\underline{\underline{\pink{SOLUTION : -}}}}}}[/tex]
[tex]\begin{gathered} \quad{\twoheadrightarrow{\tt{5(4 + x) = 3(3x - 1) - 9}}}\\\\\quad{\twoheadrightarrow{\tt{5 \times 4 + 5 \times x = 3 \times 3x - 3 \times 1 - 9}}}\\\\\quad{\twoheadrightarrow{\tt{20+ 5x = 9x - 3 - 9}}}\\\\\quad{\twoheadrightarrow{\tt{20+ 5x = 9x - 12}}}\\\\\quad{\twoheadrightarrow{\tt{9x -5x = 20 + 12}}}\\\\\quad{\twoheadrightarrow{\tt{4x =32}}}\\\\ \quad{\twoheadrightarrow{\tt{x = \dfrac{32}{4}}}} \\\\\quad{\twoheadrightarrow{\tt{\underline{\underline{x =8}}}}} \end{gathered}[/tex]
Hence, the value of x is 8.
[tex]\rule{300}{2.5}[/tex]